Determining friction and effective loading for sled sprinting. Issue 22 (17th November 2017) - Cross, Matt R.; Tinwala, Farhan; Lenetsky, Seth; Samozino, Pierre; Brughelli, Matt; Morin, Jean-Benoit
ABSTRACT: Understanding the impact of friction in sled sprinting allows the quantification of kinetic outputs and the effective loading experienced by the athlete. This study assessed changes in the coefficient of friction ( µ k ) of a sled sprint-training device with changing mass and speed to provide a means of quantifying effective loading for athletes. A common sled equipped with a load cell was towed across an athletics track using a motorised winch under variable sled mass (33.1–99.6 kg) with constant speeds (0.1 and 0.3 m · s −1 ), and with constant sled mass (55.6 kg) and varying speeds (0.1–6.0 m · s −1 ). Mean force data were analysed, with five trials performed for each condition to assess the reliability of measures. Variables were determined as reliable (ICC > 0.99, CV < 4.3%), with normal-force/friction-force and speed/coefficient of friction relationships well fitted with linear ( R 2  = 0.994–0.995) and quadratic regressions ( R 2  = 0.999), respectively ( P <  0.001). The linearity of composite friction values determined at two speeds, and the range in values from the quadratic fit ( µ k  = 0.35–0.47) suggested µ k and effective loading were dependent on instantaneous speed on athletics track surfaces. This research provides a proof-of-concept for the assessment of friction characteristics during sled towing, with a practical example of its application in determining effective loading and sled-sprinting kinetics. The results clarify effects of friction during sled sprinting and improve the accuracy of loading applications in practice and transparency of reporting in research.